Assessment of the effects of sanctions on trade between the EU and Russia - Kolářová, Andrea; Klosová, Anna, 1942-; Coniglio, Nicola; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
This thesis is trying to assess the effects of sanctions imposed on Russia in 2014 by the European Union and other countries, with respect to the changes in the trade flows among the two participants (EU and Russia). Firstly, the theoretical background for sanctions is provided, explaining their meaning and instruments which they use. Secondly, the overview of the Ukrainian conflict is conducted together with a brief review of the economic restrictions which were implemented, as well as the Russian counter-sanctions. The empirical part is firstly explaining the effects of the restrictions on the both economies and then introducing the state of the bilateral trade flows between the EU and Russia before the imposition of the sanctions. The most important part of the thesis is the gravity model conducted in the third chapter, which is trying to estimate the effects of the sanctions on the EU-Russian trade flows using two approaches. One of them is conducted with the help of regression analysis and a dummy variable which controls for the sanctions effect. The other one is predicting the values of exports without the disturbance of the sanctions and then comparing the results with the real values of the export for the years examined. The results of these analyses have proven the expectations about the negative impact of the sanctions on the trade flows between the EU and Russia.
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses